Kejadian Kecacingan pada Siswa Sekolah Dasar Negeri Kecamatan Rumbai Pesisir Pekanbar - Sri Kartini (STIKes Hang Tuah Pekanbaru, 2016)
Helminthiasis remains a health problem. This disease mostly suffered by children. Mild helminthiasis cause no symptoms, but in severe conditions can cause intestinal problems such as diarrhea and abdominal pain, malaise, decreasing cognitive and physical development, and anemia.The purpose of this study was to determine the proportion of helminthiasis and factors associated with helminthiasis i.e the habit of hand washing, nail hygiene, availability of latrines, type of floor of the house, the availability of clean water in the house, the availability of trash, a habit of playing in land, the habit of using footwear, availability of Waste Water Disposal Facility, mother's occupation, father's occupation, sex and drinking-worming in elementery school students. This study was observasional analytic study with crossectional approach. The population were 2610 students of state elementary school in Kecamatan Rumbai Pesisir. As many as 240 students obtained a sample by using systematic random sampling The date was analaized with Multiple linear regression. The results showed the proportion of helminthiasis incidence was 16.3%,which ascariasis incidence 12.9%, trichuriasis 2.5% and hookworm infection 0.8%. The Variables that significantly related to the incidence of helminthiasis were taking anthelmintics (POR: 11.143; 95% CI: 4.179 to 31.886) , handwashing (POR: 5.366; 95% CI: 2.186 to 13.172), the availability of SPAL (POR: 2.615; 95% CI: 1.195 to 6.787) and nail hygiene (POR: 2.378; 95% CI: 1.300 -7.227).